2017
DOI: 10.1038/srep44189
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous TNFα orchestrates the trafficking of neutrophils into and within lymphatic vessels during acute inflammation

Abstract: Neutrophils are recognised to play a pivotal role at the interface between innate and acquired immunities following their recruitment to inflamed tissues and lymphoid organs. While neutrophil trafficking through blood vessels has been extensively studied, the molecular mechanisms regulating their migration into the lymphatic system are still poorly understood. Here, we have analysed neutrophil-lymphatic vessel interactions in real time and in vivo using intravital confocal microscopy applied to inflamed cremas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 57 publications
5
71
0
Order By: Relevance
“…The discrepancy might be due to the fact that many other factors can affect the process of neutrophil migration. Previous studies indicated that tumour necrosis factor, intercellular cell adhesion molecule‐1, and IL‐6 can play a positive role in neutrophil migration . In this study, our RNA‐Seq analysis showed that the expression of these genes as well as neutrophils chemo‐attractants including CXCL8, CXCL1, CXCL2, CXCL3, and CXCL16 were decreased in T1D patients when compared with healthy controls.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The discrepancy might be due to the fact that many other factors can affect the process of neutrophil migration. Previous studies indicated that tumour necrosis factor, intercellular cell adhesion molecule‐1, and IL‐6 can play a positive role in neutrophil migration . In this study, our RNA‐Seq analysis showed that the expression of these genes as well as neutrophils chemo‐attractants including CXCL8, CXCL1, CXCL2, CXCL3, and CXCL16 were decreased in T1D patients when compared with healthy controls.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies indicated that tumour necrosis factor, intercellular cell adhesion molecule-1, and IL-6 can play a positive role in neutrophil migration. [32][33][34] In this study, our RNA-Seq analysis showed that the expression of these genes as well as neutrophils chemo-attractants including CXCL8, CXCL1, CXCL2, CXCL3, and CXCL16 were decreased in T1D patients when compared with healthy controls. Therefore, many other molecules in addition to CD62L may act together to mediate neutrophil migration.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have reported that an influx of neutrophils characterizes inflammation into the inflammatory area in which the cytokines play a crucial role. 22 our results indicate that WPS reduces the HS-induced inflammatory response. It could be hypothesized that WPS can protect vascular endothelial function by reducing the production of proinflammatory cytokines like IL-6 and TNF-α and decreasing the oxidative stress of inflammatory factors.…”
Section: Wsp Reduces Inflammation and Involvement Of Il-6 And Tnf-αsupporting
confidence: 70%
“…Neutrophil migration relies on lymphocyte function–associated antigen 1, an integrin/complement receptor CD11b and C-X-C or C-C chemokine receptors CXCR4 and/or CCR7 ( Fig. 1 C ; Gorlino et al, 2014 ; Hampton et al, 2015 ; Arokiasamy et al, 2017 ). Dermis also contains an abundant population of macrophages, which contributes to local control of lymphangiogenesis and lymphatic remodeling during development, inflammation, and wound healing ( Harvey and Gordon, 2012 ; Kim et al, 2014 ).…”
Section: Skin Lymphatic Vasculaturementioning
confidence: 99%